Luoghi e nonluoghi nei romanzi di Niccolò Ammaniti - Matolcsi, Balázs (Verbum – Analecta Neolatina, 2024)
Since the beginning of his career, Ammaniti has tended to choose special places for his novels: almost always imaginary places that symbolise the personal and social isolation of the characters. But in addition to these places, the Roman writer’s narrative features an increasingly massive presence of non-places, which in his most recent novels become fundamental elements of the plot and character development. Thus, on the one hand non-places play an innovative role; on the other hand they signify continuity, they represent a global level of isolation. According to my hypothesis, non-places become more and more present in Ammaniti’s novels, there is a clear shift towards their importance, to the point of constituting the backbone of the narrative. In my talk, I would like to analyse how this change, obviously driven by a significant social change, affects the plot and the characters’ behaviour; how non-places are amalgamated into the fabric of the narrative.